PERSEPSI AKADEMISI DAN PRAKTISI AKUNTANSI TERHADAP AKUNTANSI FORENSIK SEBAGAI PROFESI DI INDONESIA (Studi Empiris Pada Akademisi Dan Praktisi Akuntansi Di Kota Pekanbaru) - Yushananda, Rizki Pratama; ', Zirman; Ilham, Elfi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2016)
This research aims to get empirical prove of the difference between academician and practitioner perceptions regarding forensic accounting as a profession in Indonesia on the issues of theory and forensic accounting technique, accounting relevance in the object of this research was academics and practitioners in Pekanbaru City. Data collected from Badan Pengawas Keuangan dan Pembangunan Republik Indonesia branch of Riau Province and five Universities such as Universitas Riau, Universitas Islam Negeri Sultan Syarif Kasim, Universitas Islam Riau, Universitas Lancang Kuning dan Universitas Muhammadiyah Riau which stated in Pekanbaru City in 2015 as objects of this research. Sample of this research was determined by using probability sampling technique in data collection. Each population was represented by lecturer as the academician and auditor as the practitioner. Data was obtained by distributing 75 questionnaires with 62 respondents give their responses for further analysis. The analysis model used in this study was statistic descriptive and T Test by using SPSS version 20.0 in order to perform the hypothesis test. The result of this research partially shows that the issues of theory and intelllectual technique are significant at 0,393; relevance is significant at 0,084; training period is significant at 0,927; motivation is significant at 0,447; autonomy is significant at 0,148; commitment is significant at 0,780; sense of community is significant at 0,295; the code of ethics is significant at 0,689. The result of this research shows that there is difference in the perception between academician and practitioner in motivation and commitment variable.Keywords : Academician, Practitioner, Forensic Accounting, Profession.